2020
DOI: 10.3389/fgene.2020.580299
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-Methyltransferase Is a Prognostic Biomarker and Correlated With Immune Infiltrates in Gastric Cancer

Abstract: Gastric cancer (GC) is the third most common cause of cancer-related death in the word. Immunotherapy is a promising treatment of cancer. However, it is unclear which GC subpopulation would benefit most from immunotherapy and it is necessary to develop effective biomarkers for predicting immunotherapy response. Nicotinamide N-methyltransferase (NNMT) is a metabolic regulator of cancer-associated fibroblast (CAF) differentiation and cancer progression. In this study, we explored the correlations of NNMT to tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…In addition, by influencing the SAM/SAH ratio inside the cell, it can indirectly impact gene expression [ 69 ]. In the last two decades, NNMT has been the focus of a number of studies that demonstrated the involvement of this enzyme in the progression of numerous malignancies including oral squamous cell carcinoma (OSCC), papillary thyroid cancer, lung cancer, gastric cancer, pancreatic cancer, colorectal cancer, clear cell renal cell carcinoma (ccRCC), breast cancer, bladder urothelial carcinoma (BUC), and ovarian clear cell carcinoma [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Nicotinamide N -Methyltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by influencing the SAM/SAH ratio inside the cell, it can indirectly impact gene expression [ 69 ]. In the last two decades, NNMT has been the focus of a number of studies that demonstrated the involvement of this enzyme in the progression of numerous malignancies including oral squamous cell carcinoma (OSCC), papillary thyroid cancer, lung cancer, gastric cancer, pancreatic cancer, colorectal cancer, clear cell renal cell carcinoma (ccRCC), breast cancer, bladder urothelial carcinoma (BUC), and ovarian clear cell carcinoma [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Nicotinamide N -Methyltransferasementioning
confidence: 99%
“…In addition, by influencing the SAM/SAH ratio inside the cell, it can indirectly impact gene expression [69]. In the last two decades, NNMT has been the focus of a number of studies that demonstrated the involvement of this enzyme in the progression of numerous malignancies including oral squamous cell carcinoma (OSCC), papillary thyroid cancer, lung cancer, gastric cancer, pancreatic cancer, colorectal cancer, clear cell renal cell carcinoma (ccRCC), breast cancer, bladder urothelial carcinoma (BUC), and ovarian clear cell carcinoma [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. The analysis of NNMT expression levels in ccRCC demonstrated that the amount of upregulated enzyme is inversely correlated with tumor size, suggesting that the enzyme could play a role in cancer progression [86].…”
Section: Nicotinamide N-methyltransferasementioning
confidence: 99%
“…As for NNMT , related studies found that high NNMT expression in stromal cells may predict an unfavorable postoperative prognosis for gastric carcinoma. 35 NNMT is known to act as a negative predictor for gastric carcinoma prognosis and is correlated with immune infiltrates 36 , 37 . These findings confirmed our results, and upregulated NNMT in gastric cancer cells may promote the occurrence of epithelial‐mesenchymal transition by activating TGF‐β1/SMAD signaling, 38 thereby leading to tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Such uniformity of the stromal proteome was in marked contrast with the genetic and proteomic heterogeneity of the corresponding carcinoma compartment [37]. NNMT is a key metabolic enzyme in catalyzing the N-methylation of nicotinamide (one of the forms of vitamin B3) using the universal methyl donor S-adenosyl methionine (SAM) [38]. Notably, the overexpression of stromal NNMT in ovarian tumors led to the depletion of SAM concomitantly with DNA and histone hypomethylation, which were in turn associated with widespread gene expression alterations.…”
Section: Histone Core Modifications In Tafsmentioning
confidence: 99%
“…In agreement with this interpretation, NNMT was upregulated in TAFs in gastric and colorectal cancer [39], and is associated with poor prognosis in several solid tumors including NSCLC. Moreover, NNMT overexpression was linked with the expression of PD-L1 and other immune checkpoint markers [38,40], whereas NNMT silencing was associated with decreased tumorigenicity in NSCLC [41].…”
Section: Histone Core Modifications In Tafsmentioning
confidence: 99%